Hits and misses: water-based climate change adaptation interventions for agriculture in South Asia - Lakshmikantha, N.R.; Shah, Rinan; Srinivasan, Veena; Mukherji, Aditi (2025)
South Asia's small and marginal farmers are vulnerable to climate change. This is a pressing concern due to the region's heavy dependence on agriculture. There is an urgent need to invest in adaptations that are effective. This study conducts an in-depth analysis of climate change adaptation interventions in the context of South Asia's unique challenges.